Model of Fit Perceived Environment Uncertainty (PEU) and Budgetary Characteristics on Managerial Performance: A Residual Approach - Oktavianus Pasoloran; Adelisa Matasik; Fransiskus Randa (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study examines effects of budgetary goal characteristics that are budgetary participation, budget goal clarity, budget goal difficulty, budgetary feedback on managerial performance using regression analysis (stepwise). This study also examined the contingency theory to seen the fit between budgetary goal characteristics system and environment on organization effectiveness, in this case budgetary system and perceived environmental uncertainty (PEU) to increasing managerial performance using residual approach. The application of residual analysis is illustrated by examining the interaction fit of budgetary goal characteristics and perceived environmental uncertainty and their effect on managerial performance. Residual approach used to enhance the potential for model of fit and be unformattable for future management accounting contingency theory studies. Based on the response of 64 managers in Makassar Industrial Area. The results of the study showed that that budgetary participation and budget goal clarity tend to have positive and significant effect on managerial performance. The results related to influence of budgetary goal’s difficulty level (about right, tight but attainable, too tight) to the average of managerial performance also showed insignificant relationship. This study showed that lack of fit between budgetary participation and budgetary goal clarity to environment uncertainty have negative and significant correlation with managerial performance.